Evaluasi Keberhasilan Reklamasi Lahan Bekas Temporary Stock Batubara di PT. Bukit Asam Tbk - Hardian Aries Nugraha (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Nugraha HA. 2020. Evaluation of the success former coal temporary stock land reclamation at PT. Bukit Asam Tbk. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).PT. Bukit Asam Tbk. is a coal mining company in Muara Enim Regency, South Sumatra Province. The company has been carrying out mining activities since 1981 and has also carried out reclamation in accordance with the prevailing laws and regulations. This study aims to evaluate reclamation activities and determine the final outcome assessment in the form of the percentage of successful reclamation on the former Muara Tiga Besar coal mine Temporary Stock. The research method used is an assessment of the success rate of reclamation based on a matrix that refers to the Minister of Energy and Mineral Resources No. 1827 K / 30 / MEM Year 2018. Evaluation is carried out by comparing the planned and realized data that have been obtained in the field. From the results of data comparisons between the plan and the realization of the reclamation of the former Muara Tiga Besar coal mine, it is known that the realization of land use covering an area of 6.46 hectares or 100% of the planned area of 6.43 hectares and the realization of topsoil spreading of 6,455 m3 or 100% of the planned 6,430 m3. The realization of revegetation was 4,018 trees or 100% of the planned 4,000 trees. The results of this study indicate that the success of reclamation activities gets a total value of 99.80%. In conclusion, the success of reclamation in the former Muara Tiga Besar Mine Temporary Stock area in 2019 is included in the category of successfully meeting the assessment criteria.